The CORRELATION BETWEEN STUDENTS’ LEARNING STYLES AND STUDENTS’ SPEAKING ACHIEVEMENT - Firdathun Jannah; Slamet Asari; Nirwanto Maruf (Pascasarjana Manajemen Pendidikan Universitas Gresik, 2024)
Language learning is a multifaceted process influenced by various individual factors, including learning styles. Understanding the potential correlation between students' learning styles and their language proficiency is crucial for developing effective language teaching strategies. The primary objective of this research is to investigate whether there is a significant correlation between students' learning styles and their speaking achievement. To examine the correlation between learning styles and speaking achievement, a comprehensive speaking proficiency test was administered to 43 students. The VARK questionnaire was used to identify the prevalent learning style preferences among the participants, including Kinesthetic, Auditory, and Visual learning styles. Pearson's correlation coefficient was employed to analyze the relationship between learning styles and speaking achievement. Surprisingly, the analysis revealed no significant correlation between learning styles and speaking achievement (r = -0.12, p > 0.05). Further examination of specific learning style categories indicated that there was no significant correlation between speaking achievement and the Kinesthetic, Auditory, or Visual Learning Style preferences. These findings highlight the importance of considering multiple factors, beyond learning styles, that influence language proficiency. Language educators should adopt a comprehensive approach, incorporating diverse instructional strategies to cater to the unique needs of each student. Future research should explore the relationship between learning styles and other language skills and delve deeper into individual differences in language learning